MENINGKATKAN KEMAMPUAN BERHITUNG ANAK MELALUI PERMAINAN ULAR TANGGA DI TAMAN KANAK-KANAK AL-QUR’AN JAUHARULWATHON - Ayu Fitria Nengsih; Sukarno; Samsu (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2026)
This study aimed to improve early childhood numeracy skills through the use of the snakes and ladders game at Al-Qur'an Jauharul Wathon Kindergarten, Setiris Village, Muaro Sebo District, Muaro Jambi Regency. The problem identified in the learning process was that children showed low interest and limited understanding of counting activities because the teaching methods used were monotonous and less interactive. This research employed Classroom Action Research using the Kemmis and McTaggart model conducted in two cycles. The subjects of this study were 15 children aged 5–6 years in Group B. Data were collected through observation, interviews, and documentation. The findings revealed that the snakes and ladders game effectively improved children’s counting abilities. In the pre-cycle stage, only 13% of children achieved the expected level of numeracy development. After the implementation of the actions in Cycle I and Cycle II, children’s numeracy skills increased significantly, with most children reaching the category of developing as expected and developing very well. Therefore, the snakes and ladders game can be considered an enjoyable, interactive, and effective learning medium for improving early childhood numeracy skills.